The land of gold. Reality versus fiction. - Helper, Hinton Rowan, 1829-1909. (Baltimore, Pub. for the author, by H. Taylor, 1855)
Hinton Rowan Helper (1829-1909) of North Carolina became one of the South's most controversial figures in the 1850s for his criticisms of slavery in The land of gold and his better known book, The impending crisis. Indeed, he found it prudent to move to New York before the Civil War, and he received diplomatic appointments in Latin America from the Lincoln administration. The land of gold (1855) draws on Helper's three years residence in California and leads him to the conclusion, "California is the poorest State in the Union." Aside from gold, he can see nothing to recommend the state economically, and his book damns the state's populace in terms of morals and intelligence. He spends three chapters dismissing San Francisco (although he later has good words for the Vigilance Committee), is disgusted by the Digger Indians at Bodega, finds fault with Sacramento, and reflects on prospecting on Yuba River and at Columbia. Some good words are reserved for Stockton, but on the whole, Helper writes to discourage emigrants from retracing his course round the Horn.
Also available in digital form on the Library of Congress Web site.
Also available in digital form on the Internet Archive Web site.
Keywords: California -- Description and travel; California -- Gold discoveries; Voyages to the Pacific coast; Ethnic groups -- California; Urbanization -- California; Real estate development -- California; Law -- Political aspects -- California